Desarrollo e implementación de un portal web para gestión de courier bancarío - Arce Recalde, Jazmin (2009)
Bancourier The company is a new market which will begin its activities in the field of banking courier is providing a document delivery service, cards and announcements to customers of banking institutions that are registered as clients of the firm Bamcourier. Which aims to speed up the delivery of the documents cited above customers to make in the shortest time to achieve as many of the documents to customers of banking institutions. This company will allow the banks to know the quantity of papers, cards and account statements that were delivered to customers within the period indicated. Through a web site can be made to implement the above, since the delivery of documents is carried out online